Les préférences tarifaires canadiennes et la libéralisation des échanges - Ahmad, Jaleel (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractThe developing countries currently enjoy preferential entry on designated exports of manufactures under the Canadian Scheme of Generalized Preferences introduced in 1974. This paper makes a quantitative assessment of the erosion of such preferential margins likely to result from current multilateral tariff negotiations at GATT. Estimates are made under four alternative tariff-cutting techniques.